SIFAT FISIK GRANUL AMILUM JAGUNG YANG DIMODIFIKASI SECARA ENZIMATIS DENGAN Lactobacilus acidophilus PADA BERBAGAI WAKTU FERMENTASI - Sigit Priyanta, Rissang Bagus; Sri Arisanti, Cokorda Istri; Anton P, I G.N. Jemmy (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012)
Corn starch is the one type of starch that potential to be developed as an excipient in manufacture of pharmaceutical dosage forms. However, corn starch has the bad flow and compactibility properties. According to that matters, chemicaly modified corn starch using ? amilase enzym which is produced by Lactobacillus acidophilus highly neccesesary. It is known that ?-amylase enzyme is capable of changed the microscopic structure of starch then produced better flow rate and compactibility properties. This study was conducted to see the effect of variations in the concentration of bacteria Lactobacillus acidophilus producing ?-amilase enzime on the granule physical properties of fermented corn starch. This research was done by fermentating the corn starch using the Lactobacillus acidophilus bacteria with a variations time of fermentation which is 0, 24, 48, 72, and 84. The effect of variations time of fermentation which used Lactobacillus acidophilus on physical properties of fermented corn starch is performed by flow rate and compressibility test. The data were analyzed using one-way ANOVA with 95% confidence level. Results showed that the concentration of the Lactobacillus acidophilus bacteria significantly influence the granule physical properties of fermented corn starch. Fermented corn starch for 72 hours had been produced the best physical properties in flow rate and compactibility properties.
Keywords: corn starch, Lactobacillus acidophilus, time of fermentation, physical properties